Selected documents of the international petroleum industry : 1975/76 - Organization of Petroleum Exporting Countries (Vienna : Information Dept. of the Organization of the Petroleum Exporting Countries, 1977)
It covers the most important developments in legislation pertaining to the oil industry which have led to a further consolidation of OPEC Member Countries' control over their hydrocarbon resources.
occ 16/01/2019
Loans
Keywords: Petroleum law and legislation; Petroleum industry and trade; OPEC